2016
DOI: 10.1111/pim.12356
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel lentiviral vaccine expressing KMP11‐HASPB fusion protein against Leishmania infantum in BALB/c mice

Abstract: Hydrophilic acylated surface protein B (HASPB) is an immunogenic Leishmania protein against which antibodies are produced in the sera of cutaneous and visceral Leishmaniasis (VL) patients. Kinetoplastid membrane protein 11 (KMP11) is another protein antigen of Leishmania which is reported as a promising candidate for vaccination of VL. It is a highly conserved surface protein present in all members of kinetoplastid family and is expressed in both promastigotes and amastigotes. In this study, the coding sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Our results in the past study indicated that lentiviral vaccine expressing the KMP11-HASPB fusion protein of L. infantum is capable of inducing the immune system to produce cytokines and specific antibodies against L. infantum and resulted in decreased parasite burden (Mortazavidehkordi et al 2016). Since these two proteins have been detected in different species of Leishmania and have a high degree of similarity among species, therefore, for the first time, we developed a lentiviral DNA vaccine containing KMP11-HASPB coding sequence of L. major and evaluated its potentials in a mouse model of L. major.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Our results in the past study indicated that lentiviral vaccine expressing the KMP11-HASPB fusion protein of L. infantum is capable of inducing the immune system to produce cytokines and specific antibodies against L. infantum and resulted in decreased parasite burden (Mortazavidehkordi et al 2016). Since these two proteins have been detected in different species of Leishmania and have a high degree of similarity among species, therefore, for the first time, we developed a lentiviral DNA vaccine containing KMP11-HASPB coding sequence of L. major and evaluated its potentials in a mouse model of L. major.…”
Section: Introductionmentioning
confidence: 69%
“…Nonetheless, the cytokine pattern of the immune system against Leishmania is not perfectly clear, and both inflammatory and anti-inflammatory cytokines have been detected in the sera of Leishmaniasis patients (Kautz-Neu et al 2012). Maroof et al and Mortazavidehkordi et al who evaluated DNA vaccines against L. donovani and L. infantum, respectively, showed that KMP11 and HASPB are highly capable of stimulating mice immune system and can protect mice against the parasite (Maroof et al 2012;Mortazavidehkordi et al 2016). In the present study, we showed that KMP11-HASPB fusion protein induced the immune system of mice against L. major in that the parasite load in the lymph node and spleen of the vaccinated mice was significantly lower than that of controls (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Such studies also would address the duration of the protective response following ChimeraT/liposome vaccination and whether vaccination induces antigen-specific serum IgE antibodies. Although we and others have used qualitative ELISA to measure serum antibody levels [ 51 , 76 , 77 , 78 , 79 ], quantitative measurements of antibody levels in both mouse and human sera and examination of antigen-specific T-cell proliferative responses in cell culture would further inform the nature of the immune responses. Additionally, the parasite load could be evaluated by examining any histopathological changes in the organs and correlated with data obtained by the limiting dilution technique and RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…coding for de facto effective antigens such as KMP-11, LACK, Leish-F3 and HASPB, were tested in the pre-clinical context for both CL and VL, with promising results obtained in all animal models used (mice, dogs and macaques) [51,84,[120][121][122][123]. Remarkably, one of them was the first third-generation anti-Leishmania vaccine candidate to undergo human clinical trials.…”
Section: Third-generation Vaccine Candidatesmentioning
confidence: 99%